KONSTRUKSI KARAKTER RELIGIUS DALAM PRAKTIK SILATURRAHIM KOMUNITAS TAREKAT AN-NAQSYABANDIYAH - Aini, Innani Khofifah Qurrotu; Maghfiroh, Muliatul (Departemen Pendidikan Bahasa, Fakultas Ilmu Budaya, Universita Brawijaya, 2026)
This study analyzes the role of routine silaturrahim activities among the Brotherhood, Sisters, and Sympathizers of the An-Naqsyabandiyah Thariqot (SITQON) in Panaguan Village, Larangan District, Pamekasan Regency in shaping the religious character of the community. The study aims to explain the mechanisms of internalizing religious values through silaturrahim practices and their contribution to the formation of religious discipline and the strengthening of social and spiritual dimensions within the community. A descriptive qualitative approach was employed, with data collected through non participant observation, in depth interviews, and documentation. Data were analyzed thematically using source and technique triangulation. The findings indicate that routine SITQON silaturrahim functions as a structured space for religious habituation, enabling the internalization of religious values through repeated practice, role modeling, and sustained social interaction. Activities such as dhikr, religious sermons, and socio religious interactions foster worship discipline, moral responsibility, social awareness, and strengthened bonds of brotherhood. Silaturrahim also creates a social structure that supports the continuity of religious practices, allowing religious character to develop not only as a personal quality but also as a collectively shared social norm. The study highlights that community based silaturrahim offers a strategic model for religious character education in rural Muslim communities.